REVITALISASI PEMBELAJARAN: SOLUSI TERHADAP RENDAHNYA MINAT BELAJAR PESERTA DIDIK KELAS V SDN SUMBER AGUNG - Puri Nuralyanti; Encep Andriana; Siti Rokmanah (STKIP Subang, 2023)
This article investigates the issue of low learning interest among fifth-grade students at SDN Sumber Agung and proposes solutions through the revitalization of education. The low interest in learning can have negative impacts on academic achievement, creativity, and a positive attitude towards learning. To address these challenges, a holistic solution is suggested, involving innovative teaching methods, active parental involvement, and the improvement of school facilities. The research methodology employed is Qualitative with a Collaborative Action Research Approach. Interviews, observations, case studies, and document analysis are utilized to explore the causes of low learning interest. Some contributing factors include monotonous teaching methods, lack of parental involvement, and insufficient availability of learning materials. The proposed solutions encompass the development of interactive teaching methods, increased parental involvement, and the enhancement of the learning environment. The implementation of these solutions involves collaboration among teachers, parents, and students, with continuous monitoring and evaluation of progress. The benefits of this educational revitalization include increased interest in learning, improved examination results, and active student engagement in learning activities. In conclusion, the revitalization of education at SDN Sumber Agung is deemed a crucial step in creating a dynamic and supportive learning environment. With the involvement of all stakeholders, it is hoped that a generation of students ready to face the challenges of the modern world with a high enthusiasm for learning can be nurtured. Keywords: Low Learning Interest, Educational Revitalization, 5th Grade of SDN Sumber Agung